Forecast Daily Night Peak Electric Power Demand in Sri Lankan Power System - Ananthasingam, A.; Atputharajah, A. (IEEE, 2015)
Electricity has become vital for day today life. Electricity consumption has enormously increased during the recent past. However it cannot be conveniently stored. Therefore, at every instant of time there should be a sufficient amount of electricity generation to meet the consumer demand. Depending on the demand, power producers adjust their production level. Therefore forecasting electricity demand would be very helpful to power system operators to maintain the power quality and reliability of the power system. The highest daily electric power demand occurs in night peak in Sri Lankan power system. Therefore this paper describes forecasting the Daily Night Peak Electric Power Demand (DNPEPD) of Sri Lankan power system by using past daily data in time series analysis. Final model can be used to forecast the DNPEPD a week ahead. It is shown that the developed approach can produce more accurate results for the forecast for short term. The developed model is more beneficial for planning of a power generation pattern.
Keywords: quality; reliability